O problema da passagem do infinito para o finito nas filosofias de Schelling e Hegel - Gonçalves, Márcia (Revista Eletrônica Estudos Hegelianos, 2020)
Schelling and Hegel think the relationship between the concepts of infinite and finite in a distinct way, even though they start from a common diagnosis concerning the status of philosophical systems. This difference will be responsible for the different construction of their own philosophical systems. To explore this thematic, this article will present the development of the concept of the infinite in the youth works of the two classical German philosophers, in six different parts: (1) a brief description of the young Schelling's diagnosis of the problem of the transition from the infinite to the finite in his Letters on Dogmatism and Criticism of 1795; (2) a view of the young Schelling's interpretation of Fichte’s concept of an infinite tendency of the spirit as a possible union of the infinite and finite; (3) a discussion of the possibility of solving the problem of the infinite in Schelling's philosophy of nature; (4) a brief presentation of Hegel's interpretation of the concepts of infinity in Fichte and in Schelling in his Differenzschrift of 1801; (5) a view of the old Hegel’s solution of the problem of the infinite through his distinction between bad infinity and true infinity; (6) in conclusion, a demonstration of the difference between Hegel’s concept of bad infinity and Schelling’s concept of circular infinity.